Insects. Part G [electronic resource] : Hymenoptera and Plant Galls. - MacGillivray, Alexander Dyer, 1868-1924.; Canadian Arctic Expedition (1913-1918) (Ottawa : J. de L. Taché, 1919)
Original issued in series: Report of the Canadian Arctic Expedition (1913-1918) v. 3, pt. G. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44